PROFIL KLINIS DAN BAKTERIOLOGIS INFEKSI SALURAN KEMIH PADA ANAK DI RSUP DR. M. DJAMIL PADANG TAHUN 2017 – 2021 - Bari'ah, Puti Asma; Amelin, Fitrisia; Putra, Andani Eka; Izzah, Amirah Zatil; Welan, Rahmani (SINERGI : Jurnal Riset Ilmiah, 2025)
Urinary Tract Infection (UTI) is the most common bacterial infection in children which is characterized by an increase in bacteria in the urine. The purpose of this study was to determine the clinical and bacteriological profiles of urinary tract infection patients in children at Dr. M. Djamil Padang in 2017-2021. This type of research is descriptive with a total sample method of 52 children with a retrospective approach on patient medical record data and urine culture results. The variables studied included age, gender, nutritional status, urinary tract abnormalities, clinical symptoms, physical examination, supporting examinations, and types of bacteria in pediatric urinary tract infection patients. The results of this study showed that most cases of UTI occurred in children aged 0-1 years (59,2%) with more male cases than females, good nutritional status (56,8%), with the most congenital abnormality in males is phimosis (37,9%). Based on physical examination, it was found that most of the patients did not have a fever (50%). The results of investigations showed that the patient had leukocyturia (61,5%) on urinalysis, leukocytosis (61,5%) on blood scan, cystitis (47.8%) on ultrasound, and nephrolithiasis (33%) on CT scan. Bacterial culture results show that the most common cause of UTIs in boys is Klebsiella pneumoniae (37.9%) and in girls Escherichia coli (87.0%). Based on this study, most results were obtained in the form of uncomplicated UTI. Gram-negative bacteria are the most common type of bacteria that cause UTIs.